2013
DOI: 10.4269/ajtmh.13-0333
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Elimination of Hepatitis B Virus Transmission in Oman: Impact of Hepatitis B Vaccination

Abstract: Abstract. Approximately 2-7% of the Omani population has chronic hepatitis B virus (HBV) infection. To decrease this burden, universal childhood hepatitis B vaccination was introduced in Oman in 1990. The hepatitis B vaccination strategy and reported coverage were reviewed. To assess the impact of the program on chronic HBV seroprevalence, a nationally representative seroprevalence study was conducted in Oman in 2005. Since 1991, hepatitis B vaccination in Oman has reached almost every eligible child, with rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…This is unsurpising, given the dramatic reduction in the seroprevalence of chronic HBV infections in Oman following the successful introduction of HBV vaccination in 1990. 17 Similar findings have also been reported in Saudi Arabia. 33 Various decision analysis models have demonstrated the cost-effectiveness of HCC surveillance.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is unsurpising, given the dramatic reduction in the seroprevalence of chronic HBV infections in Oman following the successful introduction of HBV vaccination in 1990. 17 Similar findings have also been reported in Saudi Arabia. 33 Various decision analysis models have demonstrated the cost-effectiveness of HCC surveillance.…”
Section: Discussionsupporting
confidence: 78%
“…15 Moreover, prior to the introduction of mass hepatitis B vaccinations in 1990, the estimated prevalence of HBV was 2-7%. 16,17 Overall, HCC is ranked the fourth most common solid tumour among Omani male patients. 18 However, there is a lack of national data evaluating the characteristics of HCC cases.…”
mentioning
confidence: 99%
“…In 1990, Oman implemented vaccination of all newborns according to the WHO recommendation [1] . The impact on vaccination efficacy and coverage was evaluated in 2005 in a nationwide survey, showing that 15 years after introduction of HBV vaccination of newborns the prevalence of CHB in children dropped from 2.3% in 1990 to 0.5% in 2005 [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Even with the lack of evidence of hepatitis B vaccination impact among card holders in this study, evidence from other studies has shown the significant impact of hepatitis B vaccination. [32][33][34] This study had several limitations. First, the rapid test used in this study has a reported sensitivity of 95%; therefore, the HBsAg prevalence in this study might be lower than the true seroprevalence.…”
mentioning
confidence: 99%